INDONESIAN AND PHILIPPINES ENGLISH AS FOREIGN LANGUAGE STUDENTS (EFL): PERCEPTIONS AND ATTITUDES TOWARD ENGLISH LANGUAGE - Permadi, Ahmad Sapta Seno; Susanti, Elis; Munisah, Eny (Universitas Muhammadiyah Metro, 2025)
Students' perceptions and attitudes are two relevant variables in the learning process. This study is motivated by understanding students' perceptions and attitudes in learning English as a Foreign Language (EFL), especially between Indonesian and Filipino students. This study aims to analyze the attitudes of senior students in Indonesia and the Philippines towards learning English. This study compared senior high school students in Indonesia with junior high school students in the Philippines. The research method used was mixed, i.e., quantitative and qualitative methods, through filling out questionnaires and interviews to collect data from both groups of students. The results showed different perspectives between students in Indonesia and the Philippines regarding English language learning and their attitudes toward the learning process. The findings provide greater insight into the factors influencing students' views and attitudes in English language learning, which can help educators develop more effective learning measures in Indonesia..